The spatial and spatiotemporal interpersonal coordinations in aikido’s jiyu waza - Gemas Neto, Estefan; Fernandes Silva, Marcelo Tadeu; Reis , Marcos Antônio Mattos dos; Corrêa, Umberto Cesar (Revista de Artes Marciales Asiáticas, 2026)
Over the past few years, interpersonal coordination has been increasingly recognised as an important concept in understanding sports performance. It refers to the interactions between individuals. The present study aimed to investigate the interpersonal coordination in jiyu waza. Specifically, it sought to identify the spatial and spatiotemporal measures that characterised interpersonal coordination in jiyu waza. Twenty aikido practitioners participated in the study, with a mean age of 30 years (± 5 years), with a minimum rank of shodan (1st degree black belt) and a minimum of 8 years of aikido practice. The task was jiyu waza, which consisted of a defending aikido practitioner avoiding being surrounded and/or hit by three opponents. Triangular area, triangular shape/type, and interpersonal distance, together with their respective measures of change rates (variability and velocity) were used as measures of interpersonal coordination. The x and y coordinates of the participants’ displacement were obtained from 30-second filming (1800 frames at 60 fps) using the semi-automatic tracking software Kinovea 0.9.5. The filming was performed from above, considering the top of each participant’s head as the tracking point. Results revealed that: (1) the attackers’ interpersonal coordination’s in the form of scalene and obtuse triangles, with more variable areas, as well as the greater interpersonal distances between the defender and the triangles characterised the defenses; (2) the attacks in which the defender was attacked from the front, but was unable to neutralise it, were characterised by greater interpersonal distances that emerged with greater positive velocities; (3) the defender consistently failed to neutralise attacks from behind; these situations were characterised by the interpersonal coordination represented by the scalene and obtuse triangles. The findings of this study suggest that the triangular measures (area and shape/type) were able to capture the interpersonal coordination of cooperation between the attackers, and the interpersonal distance enabled access to the interpersonal coordination relative to the opposition in jiyu waza.